Children and adolescents with eating disorders during COVID‐19 confinement: Difficulties and future challenges. (29th July 2020) - Graell, Montserrat; Morón‐Nozaleda, M. Goretti; Camarneiro, Ricardo; Villaseñor, Ángel; Yáñez, Silvia; Muñoz, Rudiger; Martínez‐Núñez, Beatriz; Miguélez‐Fernández, Carolina; Muñoz, María; Faya, Mar
Abstract: Objective: To present the adaptations to treatment protocols made in a child and adolescent eating disorders (ED) unit during the eight‐week confinement period mandated in response to the COVID‐19 pandemic and examine clinical and treatment variables in the outpatient, day hospital, and inpatient care programs. Method: Description of the implementation of a combined teletherapy program for outpatient and day‐hospital patients and the adaptations made to the inpatient protocol. Retrospective review of medical records and analysis of general and specific variables related to the pandemic and confinement. Results: We held 1, 329 (73.10%) telehealth consultations and 489 (26.9%) face‐to‐face outpatient visits with 365 patients undergoing treatment in the outpatient clinic or day hospital. Twenty‐eight (7.67%) were initial evaluations. Twenty‐two patients were newly admitted and 68 ED‐related emergencies were attended. Almost half of the children and adolescents studied experienced reactivation of ED symptoms despite treatment, and severe patients (25%) presented self‐harm and suicide risk. Conclusions: The implementation of a combined teletherapy program has enabled continuity of care during confinement for children and adolescents with ED. Delivery of treatment to adolescents in the day hospital program posed the biggest challenge due to their greater degrees of severity and higher hospitalization rates. An adapted inpatient program should be maintained throughout confinement, as the need for hospitalization of children and adolescents with ED does not decrease with lockdown.